2017
DOI: 10.1007/s00335-017-9680-0
|View full text |Cite
|
Sign up to set email alerts
|

Mild reproductive impact of a Y chromosome deletion on a C57BL/6J substrain

Abstract: A recently reported deletion of about 40 Mb in length between 6.12/6.57 and 46.73/47.31 Mb on the Y chromosome long arm of the C57BL/6JBomTac inbred strain made us closely examine the strain’s breeding history and reproductive characteristics. We verified that the two copies of Rbm31y that are present inside the putative deletion were indeed deleted. This inbred strain presents an expected litter size for a C57BL/6 substrain. In vitro fertilization (IVF) efficiency and breeding efficiencies are comparable to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
(61 reference statements)
0
7
0
Order By: Relevance
“…Larson et al (2016a) have shown that, in spermatids from reciprocal F 1 hybrids between domesticus and musculus that are “mismatched” for Slx/Slxl1 and Sly , global X-chromosome expression is indeed perturbed in the direction predicted by the copy number and actions of SLX/SLX1 and SLY. Second, several independent deletions of Yq in laboratory stocks converge on a similar phenotype, namely low fertility, abnormal sperm morphology due to problems with chromatin compaction, and sex-ratio distortion in favor of females (Styrna et al 1991; Conway et al 1994; Touré et al 2004; Fischer et al 2016; MacBride et al 2017). Third, Y chromosomes from musculus — the subspecies with highest Sly copy number — are more successful at introgressing across domesticus-musculus hybrid zone in Europe, and in localities where they do, the census sex ratio is shifted towards males (Macholán et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Larson et al (2016a) have shown that, in spermatids from reciprocal F 1 hybrids between domesticus and musculus that are “mismatched” for Slx/Slxl1 and Sly , global X-chromosome expression is indeed perturbed in the direction predicted by the copy number and actions of SLX/SLX1 and SLY. Second, several independent deletions of Yq in laboratory stocks converge on a similar phenotype, namely low fertility, abnormal sperm morphology due to problems with chromatin compaction, and sex-ratio distortion in favor of females (Styrna et al 1991; Conway et al 1994; Touré et al 2004; Fischer et al 2016; MacBride et al 2017). Third, Y chromosomes from musculus — the subspecies with highest Sly copy number — are more successful at introgressing across domesticus-musculus hybrid zone in Europe, and in localities where they do, the census sex ratio is shifted towards males (Macholán et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…This is ascribed to a rampant and ongoing genomic conflict between the X and Y chromosomes over the control of offspring sex ratio. Partial deletions of the long arm of the Y chromosome (Yq) lead to sperm head malformation, sperm DNA damage, overexpression of sex-linked genes in spermatids and either a distorted offspring sex ratio in favour of females (for smaller deletions) or sterility (for larger deletions) [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Competition between Slx and Sly has led to a runaway "arms race" between the chromosomes that drives massive amplification of competing X / Y gene complexes, and also of any autosomal loci embroiled in the conflict. The signs of this conflict have now been observed at the molecular genetic level in the form of opposing transcriptional regulatory consequences of Slx / Sly depletion [4,[9][10][11]13,14]; at the cellular biological level in the form of Slx / Sly competition for intracellular binding targets [14][15][16][17]; at the organism level in the form of sex ratio skewing in Yq-deleted animals, transgenic Slx / Sly knockdown animals and various Y chromosome congenic males [3,5,6,11,18]; at the ecological level in the form of population sex ratio skewing in introgression zones between subspecies with different copy numbers of the Yborne amplicons [19,20]; and at the evolutionary population genetic level in the form of correlated co-amplification of gene families and recurrent selective sweeps at X and Y-linked amplicons [13,[21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sex-linked ampliconic transcriptional regulators Slx and Sly [3, 4, 5, 6, 7] have opposing effects on global transcription levels of the sex chromosomes in haploid spermatids via regulation of postmeiotic sex chromatin (PMSC) [8, 9, 10, 11] and opposing effects on offspring sex ratio. Partial deletions of the Y chromosome (Yq) that reduce Sly copy number lead to global overexpression of sex-linked genes in spermatids and either a distorted sex ratio in favor of females (smaller deletions) or sterility (larger deletions) [12, 13, 14, 15, 16]. Despite a large body of work studying the role of the sex chromosomes in regulating spermatogenesis (recent reviews [17, 18, 19, 20]), most studies do not address differential fertility effects on X- and Y-bearing cells.…”
mentioning
confidence: 99%